Acute toxicity of two pesticides Diazinon and Deltamethrin on Tench (Tinca tinca) larvae and fingerling - Mohammad Forouhar Vajargah; Sayede Amene Hossaini; Elaheh Hassan Nataje Niazie; Aliakbar Hedayati; Mohammad Javad Vesaghi (International Journal of Aquatic Biology, 2013)
Diazinon and deltamethrin are common useful agricultural pesticides in the world. The present research compared the acute toxicity of diazinon and deltamethrin to tench larvae and fingerling. LC50 of 24 h, 48-h, 72 h and 96 h were determined using a probit. Fish samples (21 fish in each test group) were exposed to different concentrations of diazinon and deltamethrin (diazinon: for fingerling between1-20 ppm and larvae 0.25-2 ppm, deltamethrin: for fingerling between 0.01-0.2 ppm and larvae 0.0025-0.02) for 96 h and mortality were recorded. The LC50 96 h of diazinon for fingerlings and larvae were 6.77 and 0.63, respectively. The LC50 96 h of deltamethrin for fingerlings and larvae were 0.07 and 0.005 ppm, respectively. According to the results, larvae are more sensitive than fingerlings, LC50 values indicated that deltamethrin is more toxic than diazinon to Tinca tinca, so we suggest to use diazinon instead of deltamethrin in agriculture.